2019
DOI: 10.1590/2175-8239-jbn-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for major infections in hospitalized children with nephrotic syndrome

Abstract: Introduction: Children with nephrotic syndrome are at increased risk of infections because of disease status itself and use of various immunosuppressive agents. In majority, infections trigger relapses requiring hospitalization with increased risk of morbidity and mortality. This study aimed to determine the incidence, spectrum, and risk factors for major infections in hospitalized children with nephrotic syndrome. Methods: All consecutive hospitalized children between 1-12 years of age with nephrotic syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 14 publications
6
29
1
3
Order By: Relevance
“…While no randomized controlled trial has investigated the efficacy of antibiotic prophylaxis in preventing SBI in children with NS, SBI in patients on prophylaxis and SBI caused by penicillin-resistant Streptococcus pneumoniae have been reported. 13,17,32 Our study showed no benefit for antibiotic prophylaxis or pneumococcal vaccination in preventing SBI in nephrotic children who were admitted for fever, but due the selection bias, which was mentioned above, it cannot rule out an overall benefit of these measures in SBI prevention.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While no randomized controlled trial has investigated the efficacy of antibiotic prophylaxis in preventing SBI in children with NS, SBI in patients on prophylaxis and SBI caused by penicillin-resistant Streptococcus pneumoniae have been reported. 13,17,32 Our study showed no benefit for antibiotic prophylaxis or pneumococcal vaccination in preventing SBI in nephrotic children who were admitted for fever, but due the selection bias, which was mentioned above, it cannot rule out an overall benefit of these measures in SBI prevention.…”
Section: Discussionmentioning
confidence: 66%
“…This is in contrast to previous studies in which the incidence of peritonitis was higher: up to 16% of infections and 50% of SBI. [19][20][21][22]32 The relatively low incidence of peritonitis in our study could plausibly be due to the widespread use in our population of pneumococcal vaccination and prophylactic antibiotic therapy, which are directed against Streptococcus pneumoniae, the major causative pathogen of peritonitis in children with NS. The use of these measures was not associated with a lower risk of SBI in our study, but since it included only febrile patients who were admitted to hospital it is possible that these measures have prevented febrile infections including SBI in the general NS population (selection bias).…”
Section: Discussionmentioning
confidence: 99%
“…The infectious complications, especially primary peritonitis, are well-known alarming situation in children with NS. Studies have shown incidence of peritonitis in childhood NS ranging from 2.6% to 26.0% [7][8][9][10]. Patients with NS have a defective immune response due to increased urinary losses of complement factor B, low IgG levels, inadequate opsonization and impaired T-cell function [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Infections are the chief complication in patients with SSNS, accounting for 19-44% of hospitalizations [115][116][117][118][119][120].…”
Section: Rationalementioning
confidence: 99%
“…Contributing factors include the use of immunosuppressive agents, anasarca, and urinary losses of IgG and complement factors, that predispose to infection with encapsulated organisms [121]. Peritonitis is the most common severe infection, followed by pneumonia and cellulitis [115][116][117][118][119].…”
Section: Rationalementioning
confidence: 99%